Follow My Leader: The Boys of Templeton - Reed, Talbot Baines, 1852-1893; Stacey, W. S. (Walter S.), 1846-1929 (Salt Lake City, UT : Project Gutenberg, 2007)
"Follow My Leader: The Boys of Templeton" by Talbot Baines Reed is a novel written in the late 19th century. The story revolves around three young boys, Richardson, Heathcote, and Coote, who are preparing for an important examination at Templeton School, a prestigious institution that will determine their future. As they navigate the pressures of adolescence and the threshold of a new chapter in their lives, the themes of friendship, bravery, and personal growth are explored. The opening of the book introduces the three boys on a cold spring morning as they embark on their crucial journey to Templeton School. Set against the whimsical backdrop of school life, they are filled with a mix of excitement and anxiety about the impending examination. Their interactions depict the innocence and camaraderie that often characterize childhood friendships. From fumbling with historical trivia to joking about their uncertain futures, the boys$1 (Bdialogue captures their youthful anxieties, setting the stage for an adventure filled with challenges and mischief as they strive to prove themselves in a new environment. (This is an automatically generated summary.)s
Release date is 2007-04-05
Produced by Nick Hodson of London, England
Keywords: Schools -- Fiction; Conduct of life -- Juvenile fiction; Boarding schools -- England -- Juvenile fiction; Students -- Social life and customs -- Juvenile fiction